2009
DOI: 10.1029/2008ja014036
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative estimates of the slab and 2‐D power in solar wind turbulence using multispacecraft data

Abstract: [1] A quantitative estimate of the field-aligned anisotropy of magnetohydrodynamic inertial range turbulence is obtained by comparing multispacecraft data with a fully threedimensional turbulent magnetic field numerical model. The simulated turbulence is a superposition of slab fluctuations parallel to the mean field and 2-D fluctuations perpendicular to it. This model is fitted to spatial autocorrelation functions, computed from measurements made by the four Cluster spacecraft in the solar wind, by varying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…Moreover, in the inner heliosphere, there is only weak distance or wind speed dependence in the results, at least towards the high-frequency end of the inertial range [45,46]. Slab + 2D-type fits similar to equation (3.1) have been widely used [48][49][50]53,[60][61][62] and these also report high values for the inertial range two-dimensional fraction, e.g. 70-100%.…”
Section: (A) Review Of Observationsmentioning
confidence: 99%
“…Moreover, in the inner heliosphere, there is only weak distance or wind speed dependence in the results, at least towards the high-frequency end of the inertial range [45,46]. Slab + 2D-type fits similar to equation (3.1) have been widely used [48][49][50]53,[60][61][62] and these also report high values for the inertial range two-dimensional fraction, e.g. 70-100%.…”
Section: (A) Review Of Observationsmentioning
confidence: 99%
“…On the other hand, observations also suggested that turbulence was present and may have contributed to heating [e.g., Coleman, 1968]. Subsequent observational studies indicated that at magnetohydrodynamic (MHD) scales there are at least two distinct types of fluctuation and that the wave-like energy may be a minor component Bieber et al, 1996;Milano et al, 2004;Dasso et al, 2005;Horbury et al, 2005Horbury et al, , 2008Podesta, 2009;Osman and Horbury, 2009;Narita et al, 2010]. This encouraged development of more complete transport theories for the energy-containing range quantities [e.g., Tu and Marsch, 1993;Matthaeus et al, 1994Matthaeus et al, , 1996Matthaeus et al, , 1999Matthaeus et al, , 2004Zank et al, 1996;Smith et al, 2001Smith et al, , 2006Isenberg et al, 2003Isenberg et al, , 2010aIsenberg, 2005;Breech et al, 2005Breech et al, , 2008Yokoi and Hamba, 2007;Usmanov and Goldstein, 2010;Ng et al, 2010], in which turbulence properties are built in, contrasting with WKB theory, in which the waves are noninteracting at leading order.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the partitioning of the total fluctuation energy into its Z 2 and W 2 components must also be specified. Here we assume that 80% of the fluctuation energy is in the quasi-2-D component [Bieber et al, 1996;Osman and Horbury, 2009]. This percentage of 2-D fluctuations is most appropriate to slow wind .…”
Section: Solutions With Time-varying Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (1) can be ignored, and then R(r, τ) becomes a function of r alone. A computation of the correlation function taking into account the pure spatial lag, using simultaneous observations from two spacecraft located at a proper spatial separation, have been done recently by the first time [16,17,18]; a good agreement with the classical techniques assuming the Taylor hypothesis, analyzing single spacecraft observations as done in this work, has been found [19]. In this fashion we employ a Blackman-Tukey technique to compute each correlation function R I in the same way as done in [20].…”
Section: Discussionmentioning
confidence: 99%